Extended Chain of Domination Parameters in Graphs. (26th September 2013) - Hamid, I. Sahul; Balamurugan, S.
Abstract : A subset S of the vertex set V ( G ) of a graph G is called an isolate set if the subgraph induced by S has an isolated vertex. The subset S is called an isolate dominating set if it is both isolate and dominating. Also, S is called an isolate irredundant set if it is both isolate and irredundant. In this paper, we establish a chain connecting various isolate parameters with the existing domination parameters and discuss equality among the parameters in the extended chain.